Projecting the effects of long-term care policy on the labor market participation of primary informal family caregivers of elderly with disability: insights from a dynamic simulation model. Issue 1 (December 2016) - Ansah, John; Matchar, David; Malhotra, Rahul; Love, Sean; Liu, Chang; Do, Young
Abstract Background Using Singapore as a case study, this paper aims to understand the effects of the current long-term care policy and various alternative policy options on the labor market participation of primary informal family caregivers of elderly with disability. Methods A model of the long-term care system in Singapore was developed using System Dynamics methodology. Results Under the current long-term care policy, by 2030, 6.9 percent of primary informal family caregivers (0.34 percent of the domestic labor supply) are expected to withdraw from the labor market. Alternative policy options reduce primary informal family caregiver labor market withdrawal; however, the number of workers required to scale up long-term care services is greater than the number of caregivers who can be expected to return to the labor market. Conclusions Policymakers may face a dilemma between admitting more foreign workers to provide long-term care services and depending on primary informal family caregivers.